2012
DOI: 10.1111/j.1365-294x.2012.05479.x
|View full text |Cite
|
Sign up to set email alerts
|

The genetic differentiation at quantitative trait loci under local adaptation

Abstract: Most adaptive traits are controlled by large number of genes that may all together be the targets of selection. Adaptation may thus involve multiple but not necessarily substantial allele frequency changes. This has important consequences for the detection of selected loci and implies that a quantitative genetics framework may be more appropriate than the classical 'selective sweep' paradigm. Preferred methods to detect loci involved in local adaptation are based on the detection of 'outlier' values of the all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
331
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(356 citation statements)
references
References 115 publications
14
331
0
Order By: Relevance
“…On the other hand, more recent simulations suggest that high population differentiation can result in a higher rate of false-negatives [41], yet our study still found greater evidence for selection signatures in pairwise comparisons involving small populations.…”
Section: (A) Possible Caveats and Assumptionsmentioning
confidence: 44%
“…On the other hand, more recent simulations suggest that high population differentiation can result in a higher rate of false-negatives [41], yet our study still found greater evidence for selection signatures in pairwise comparisons involving small populations.…”
Section: (A) Possible Caveats and Assumptionsmentioning
confidence: 44%
“…(2016), we detected a relatively large number of significant GEAs using single‐locus analyses (Bayenv2 and LFMM). F ST outlier and GEA methods are more likely to detect moderate to strongly selected alleles because among‐population differentiation for weakly selected alleles is very difficult to distinguish from neutrally evolving loci (Le Corre & Kremer, 2012; Lotterhos & Whitlock, 2015; Yeaman, 2015). Given the small proportion of the genome surveyed here, it seems unlikely that we captured a significant amount of adaptive covariance among loci, and so we abstain from drawing conclusions about the genetic architecture of local adaptation to climate in P. strobus .…”
Section: Discussionmentioning
confidence: 99%
“…This could be overly conservative at times, as power to detect Q ST 4F ST is generally limited for species with high neutral genetic divergence (Porcher et al, 2006;Le Corre and Kremer, 2012). Moreover, several improved estimation approaches are currently not applicable for selfing species with high neutral divergence (personal communication M. Karhunen;Whitlock, 2008;Karhunen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%